EFFECTS OF SELECTED MACROECONOMIC VARIABLES ON DIASPORA REMITTANCES IN KENYA FOR THE PERIOD 1980 TO 2016 - ONONO, PEREZ; Mohammed, ABBA (Advances in Social Sciences Research Journal, 2020)
This study investigated the effect of selected macroeconomic variables on diaspora remittances in Kenya. Earlier studies for Kenya on diaspora remittances have focused mainly on the importance of foreign remittances on economic growth and stock market performance with less focus on macroeconomic variables that drives the remittances. In particular, the study determined the effect of economic growth, interest rates, and openness of the economy, interest rates differential and exchange rates on diaspora remittances in Kenya for the period 1980 – 2016 based on quarterly data. The study found that currency depreciation increases diaspora remittances. Similarly, economic growth, financail sector development and openness of the economy were shown to increase diaspora remittances. Based on the findings, the study recommends the need for effective application of prudent macroeconomic policies to attract more diaspora remittances inflows. In addition, there is need to adopt policies geared towards financial sector development such as the policies on formalization of the informal financial services, leveraging on the technology for financial sector development. Lastly, establishing more economic ties beyond trade with other economies to address issues on the taxation and other charges on the remitting funds from abroad would go a long way in promoting diaspora remittances inflows.